Biomass-Based Polymer Nanoparticles With Aggregation-Induced Fluorescence Emission for Cell Imaging and Detection of Fe3+ Ions - Han, Shiyan; Ni, Jiaxin; Han, Youqi; Ge, Min; Zhang, Chunlei; Jiang, Guiquan; Peng, Zhibin; Cao, Jun; Li, Shujun (Frontiers in Chemistry, 2020)
Polymeric nanoparticles, which show aggregation-induced luminescence emission, have been successfully prepared from larch bark, a natural renewable biomass resource, in a simple, rapid ultrasonic fragmentation method. The structure, element, particle size and molecular weight distribution of larch bark extracts (LBE) were studied by FTIR, XPS, TEM, XRD and linear mode mass spectrometry, respectively. LBE was found containing large numbers of aromatic rings, displaying an average particle size of about 4.5 nm and mainly presenting tetramers proanthocyanidins. High concentration, poor solvent, low temperature and high viscosity restricted the rotation and vibration of the aromatic rings in LBE, leading to the formation of J-aggregates and enhancing the aggregation-induced fluorescence emission. LBE possessed good resistance to photobleaching under ultraviolet light (200 mW/m2). Cytotoxicity experiments for 24 h and flow cytometry experiments for 3 days proved that even the concentrations of LBE as high as 1 mg/mL displayed non-toxic to MG-63 cells. Therefore, LBE could be employed for MG-63 cell imaging, with similar nuclear staining to the DAPI. The effects of different metal ions on the fluorescence emission intensity of LBE were analyzed and exhibited that Fe3+ owned obvious fluorescence quenching effect on LBE, while other metal ions possessed little or weak effect. Furthermore, the limit of detection (LOD) of Fe3+ was evaluated as 0.17 μM.